Kompetensi Kepribadian Diri Guru di Pesantren - Bagas Nirwana Selian; Ainal Mardhiah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to analyze the personality competencies of teachers in Islamic boarding schools. The research method used is descriptive qualitative, data collection is carried out through observation, questionnaires and documentation. The research results show that teachers at the Sulaymaniah Blang Bintang Islamic Boarding School have good personality competencies, which are reflected in their attitudes, values ​​and behavior. A positive attitude, integrity and teacher example are important elements in creating a conducive learning environment. Apart from that, the teacher's ability to communicate and manage emotions also contributes to harmonious interactions with students. This research confirms that teacher personality competencies not only influence the quality of teaching, but also play an important role in forming the character of students, so it is important for educational institutions to continue to support the development of these competencies through training and professional development programs.